Pembuatan Taman Edukasi Toga (Tanaman Obat Keluarga) Di Desa Larangankulon Kecamatan Mojotengah Kabupaten Wonosobo - Niken Kencono Ungu; Imam Tegar Faezhal; Dwi Ayu Febriyanti; Ika Pujianti; Afi Dwi Nur Indriyni; Elis Muhmmad Alwi Mubarok Ns; Qodam Qodam; Indi Suryaningrum; Muchamad Nadzif; Ita Umiyati; Alif Maulana (Jurnal Pengabdian Masyarakat Madani, 2022)
Larangankulon is a village located in Mojotengah sub-district, Wonosobo district, Central Java, Indonesia. The geographical location of Larangankulon Village is in the Northeast of Wonosobo Regency. To the north it is bordered by Kleyang Jurang Village, to the south by Kejiwan Village, to the west by Bumiroso Village, and to the east by Sukorejo Village. The center of village government activities is in the middle of the Larangankulon Village area. Road access to Larangankulon Village is very easy with the support of easy transportation facilities. Larangankulon Village is 6 km from the district capital, with an area of ​​0.91 km2 Larangankulon Village. or 2.02% of the total area of ​​Mojotengah District, this village consists of 4 hamlets consisting of 11 RT and 5 RW. Medicinal plants must be produced naturally or environmentally friendly, must be free from chemicals so that their cultivation must be organic. Medicinal plants are more efficacious when used fresh. To avoid the negative impact of the use of medicinal plants for disease sufferers, the selection of types and materials of medicinal plants must be properly and correctly according to the indications of the disease. The problems faced are: 1) there is still a lack of extensive use of fertile land by the community 2). Cultivating and utilizing existing local potential, 3) limited Knowledge & Skills, 4) Natural vegetation, 5) lack of skills possessed by out of school girls. Based on this basis, it was agreed to implement the TOGA Educational Park. The purpose of the activity is to utilize the potential of the Toga plant which will fill, fill most of the remaining land/home fencing which will become a living pharmacy with very large benefits and its designation is to fulfill preventive (prevention), promotive (health promotion) and curative (treatment) efforts. utilizing part of the land to be planted with toga plants which are efficacious as traditional medicine that can be used to treat various diseases, it has a very large utility if it can be used as a living pharmacy by utilizing a piece of leftover land in the yard of the house, with this KPM activity, it is expected can increase the degree of healthy living and people's income will increase. Herbal medicine must be produced naturally or environmentally friendly, must be free from chemicals so that its cultivation must be organic. Medicinal plants are more efficacious when used fresh. So if planted in the yard of the house besides functioning as a garden, medicinal plants can also be a source of oxygen and a source of food. To avoid the negative consequences of using medicinal plants for people with disease, the selection of types and materials of medicinal plants must be properly and correctly according to the indications of the disease. The methods used are training, mentoring, lectures, practice and demonstrations. This KPM activity also involves partner institutions of the Larangankulon Village PKK group, the Larangankulon Village Community. The number of students involved is 10 people. Keywords: Toga Plant, Life Pharmacy, Herbal Medicine, Public Health, Larangankulon Village